Microbial recognition and the immune response - Philpott, Dana (Henry Stewart Talks, 2009)
How can our cells tell that something is foreign?, Overview of innate immunity, Cell signaling PRMs, Toll-like receptors, Shigella flexneri, NLRs are related to plant R proteins involved in disease resistance, NLRs: detectors of MAMPs and danger signals, Proposed mechanism for Nod protein activation by a MAMP, Alerting the cell: Nod1 activates NFkB, Critical role of Nod1 in infected intestinal epithelial cells, Proposed mechanism for NLRP protein activation by a DAMP, The inflammasomes, How do innate immune signals translate into adaptive immune responses?, Implication of Nod1 and Nod2 in adaptive immune responses, TLRs vs. Nods, Nod1 is required for priming adaptive immunity, What is the compartment that carries Nod1-specific function?
Updated at 2020/07/15